The effects of Rht semi-dwarfing alleles on agronomic traits in Korean wheat cultivars - Cho, Eun. Jin; Kang, Chon-Sik; Yoon, Young Mi; Park, Chul Soo (The Indian Journal of Genetics and Plant Breeding, 2016)
The allelic variation at Rht-B1, Rht-D1 and Rht8 loci of Korean wheat cultivars was determined to evaluate the relationship between agronomic traits and different Rht alleles. Korean wheat cultivars had high frequency of Rht-B1a (70.4%) and Rht-D1a (51.9%) alleles. Thirteen cultivars carried both RhtB1a and Rht-D1b alleles but no cultivar carried both RhtB1b and Rht-D1b alleles. Only two cultivars, Namhae and Ol, showed 206bp fragment and whereas remaining genotypes showed 196bp at Rht8 loci. Cultivars carrying Rht-D1a and Rht8196bp alleles exhibited higher thousand kernel weight and test weight (40.2g and 809.9g, respectively) as compared to their counterpart alleles (36.6g and 788.1g, respectively). Cultivars carrying Rht-B1a and Rht-D1a alleles showed lower number of kernels per spike than those with other alleles at Rht-B1 and Rht-D1 loci. Cultivars, Namhae and Ol, carrying Rht8206bp allele showed lower test weight regardless the allelic compositions at Rht-B1 and Rht-D1 loci. Significant differences were recorded in culm and spike length regardless of allelic variation of these semi-dwarf genes.